2011
DOI: 10.1002/clen.200900212
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vegetation Characteristics on Soil Denitrification in Shoreline Wetlands of the Danjiangkou Reservoir in China

Abstract: Soil denitrification in reservoir shoreline wetlands is an important process for removing excess inorganic nitrogen from upland runoff and controlling eutrophication in aquatic ecosystems. As yet, little is known about the influence of vegetation characteristics on the soil denitrification potential in reservoir shoreline wetlands, although vegetation can affect both denitrifying bacteria and soil properties. In this study, we measured the spatial variability of denitrification enzyme activity (DEA) using acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 46 publications
2
33
0
Order By: Relevance
“…2a, [16]), suggesting that microbial composition and their functioning had large interannual variations [25] and that microbial nitrate (belowground biomass) production increased with the growth of plants [29,30]. Our finding is consistent with the literature reporting higher nitrification rates in communities with higher plant SR [1,22]. Meanwhile, plants can greatly contribute to N removals in CWs by affecting nitrification and denitrification intensity in the root zones [31][32][33][34].…”
Section: Effects Of Species Richness On Substrate Inorganic N Concentsupporting
confidence: 87%
See 1 more Smart Citation
“…2a, [16]), suggesting that microbial composition and their functioning had large interannual variations [25] and that microbial nitrate (belowground biomass) production increased with the growth of plants [29,30]. Our finding is consistent with the literature reporting higher nitrification rates in communities with higher plant SR [1,22]. Meanwhile, plants can greatly contribute to N removals in CWs by affecting nitrification and denitrification intensity in the root zones [31][32][33][34].…”
Section: Effects Of Species Richness On Substrate Inorganic N Concentsupporting
confidence: 87%
“…The amount of substrate inorganic N depends on many processes including plant uptake, ammonification, and nitrification, denitrification, and microbial immobilization of N [20][21][22][23]. Substrate nitrate and ammonium concentrations in this study were similar to those in plots with pure legumes in the biodiversity experiment in Palmborg et al [7], and was significantly higher than those in N-limited grassland diversity experiments reported in SchererLorenzen [24] and Fornara and Tilman [1] (Tab.…”
Section: Effects Of Species Richness On Substrate Inorganic N Concentsupporting
confidence: 64%
“…Denitrification in riparian zones is directly influenced by many soil physical and chemical properties, such as pH, temperature, water content, and available carbon and nitrogen (Groffman and Crawford, 2003;Burgin et al, 2010;Liu et al, 2011;Wang et al, 2013). Hunt et al (2004) indicated that the content of soil total nitrogen was the most important predictor of denitrification in a forested riparian zone, accounting for 51-82% of the total variance.…”
Section: Introductionmentioning
confidence: 99%
“…Plant residues enrich the soil nutrients, and the highest denitrification efficiency is generally found in the topsoil. Some studies found no significant differences in the topsoil denitrification enzyme activity (DEA) under different vegetation covers (Priha et al, 1999;Dhondt et al, 2004), while others found that plant biomass and vegetation significantly positively affect the topsoil DEA (Liu et al, 2011). Plant root growth has a significant influence on the DEA in the deep soil layers (Dhondt et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Wetlands have been widely acknowledged as the important regions to improve the water quality through plant uptake and microbial immobilization of excess nutrients via soil denitrification. The nitrogen amount reduced by plant uptake and microbial immobilization is returned to soils when the environmental conditions are changed (Liu et al, 2011). Microbially-mediated denitrification is the main process to remove nitrogen permanently in significant amounts from the wetlands (Howarth et al, 1996;Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%